COMBATING HARASSMENT UNDER THE PROTECTION FROM HARASSMENT ACT 17 OF 2011 IN SOUTH AFRICA: DOES IT PUNISH VICTIMS AND PROTECT PERPETRATORS? - Bronwyn Le-Ann Batchelor; Shelton Tapiwa Mota Makore (Obiter, 2021)
The Protection from Harassment Act 17 of 2011 (the Act) seeks to protect victims of harassment. Despite this legislative development, the effectiveness of the Act has not been widely explored. This article fills this cavity. It argues that the broadly drafted definition of harassment, together with other concomitant shortcomings in the Act, makes it prone to abuse by unscrupulous litigants, thereby militating against its regulatory efficiency goals. The article further maintains that the Act is constructed in an unbalanced manner as it protects the rights of complainants, but unintentionally is open to abuse, allowing, unfathomably, an alleged victim of harassment to become the harasser. The article analyses the regulatory aptness of the Act in an age marked by an exponential increase in cyber-related harassment and makes a case for enhancing the regulatory approach of the Act to offer an effective means of protecting victims of harassment in a rapidly evolving society.